The Brazilian army and the low prevalence of sexually transmitted infections in women of the military garrison of Campinas between 2017 to 2020: a prospective, cross-sectional epidemiological study - Lopes, Fabia; Tso, Fernanda Kesselring; Speck, Neila Maria de Góis (São Paulo Medical Journal, 2025)
BACKGROUND: Given the characteristics of military missions, intense interpersonal contact, and wide variation in casual relationships, the military has long been recognized as a high-risk population for sexually transmitted infections (STIs). OBJECTIVE: To assess the prevalence of STIs and socioepidemiological profile of women in the military garrison of Campinas. DESIGN AND SETTING: This prospective, cross-sectional epidemiological study, assisted by the Health Fund in the military garrison of Campinas, assessed the prevalence of human immunodeficiency virus (HIV), hepatitis B and C, syphilis, human papillomavirus (HPV), chlamydia, and gonococcus in military women or companions of soldiers with active or previously active sexual life. METHODS: This study included 647 women based on the non-inclusion criteria. They underwent clinical and laboratory tests for diagnosis of STIs. For statistical analysis, patients were divided into groups according to the presence or absence of STIs and into age groups. RESULTS: Most women were military dependents, and the majority were asymptomatic. The prevalence of STIs, in ascending order, was 0.3% for hepatitis B and C, 0.62% for syphilis, 0.62% for gonorrhea, 1.08% for chlamydia, and 2.63% for HPV. There were no cases of HIV infection. CONCLUSIONS: The Brazilian Army has the most women-like dependents in the military, belonging to the hierarchical circle of the squares. Early onset of sexual activity favored STIs approximately twice, and younger women had approximately seven times more chlamydia infections. In the general population studied, the prevalence of STIs was lower than expected than in the armed forces of other nations.